Factors Affecting graduate Students' Academic Achievement of Tribhuvan University (NPRC Journal of Multidisciplinary Research, 2025)
The present research study was design to investigate the factors affecting academic performance of graduate students of Tribhuvan university of Nepal. The variables under consideration were the academic performance (student’s grades/marks) as a dependent variable and the gender, age, schooling, father/guardian social economic status, and residential area, medium of schooling; tuition trend, daily study hours and accommodation trend were independent variables. The data were collected from 335 students through separate structured questionnaire from different collages of Tribhuvan University of Nepal using the simple random sampling technique. For analysis, correlation analysis, and descriptive analysis were used. The findings revealed that age, father/guardian social economic status and daily study hours significantly contribute the academic performance of graduate students.